Nearshoring of US manufacturing corporates’ supply chains: exploring administrative and economic issues for their potential expansion across the Americas - González Bravo, Yoel Modesto (Latin American Journal of Trade Policy, 2022)
This article explores the main issues in relation to the current trend towards the deglobalization of supply chains. Specifically, it investigates the nearshoring from China of manufacture activities, mostly intermediate industrial goods, by US corporates, and how the Americas can best take advantage of this trend. This relocation into the region represents an important opportunity to speed up its economic development. For this purpose, the regional economic and administrative readiness for this trend will be explored based on the CAGE model proposed by Ghemawat (2007) to identify key areas for further improvements to enhance the regional nearshoring potential.